Utilization of work environment safety measures among nursing staff: its relation to their performance - M. Safan, Sanaa; A. Nassar, Rehab (International Journal of Nursing Research, 2023)
Creating a healthy work environment not only is the proper thing to do, but it also benefits for the employer, accidents results from two broad causes: unsafe work condition (physical and environmental) and unsafe work behavior. Aim: to assess utilization of work environment safety measures among nursing staff: Its relation to their performance. Design: Descriptive co-relational design was used. Settings: The study was conducted at Menofia University Hospitals and Nasser Institute Hospital at critical care units and general departments. Subjects: A convenience sample of (100) staff nurses (50 from the Menofia University Hospitals and 50 from Nasser Institute Hospital) and all head nurses (12) worked in the study setting. Tools: Observation checklist for work environment safety measure. And observational Checklist for nursing staff performance regarding utilization of safety work environment measures. Results: Both hospitals were located in the category (B) in hospital safety index. Additionally, the level of nursing staff' performance in the study setting was low throughout the observation period. And also, nursing staff performance score regarding utilization of work environment safety measure at Nasser Institute Hospital was better than Menofia University Hospitals. Conclusion: At both hospitals, utilization of work environment safety measures is positively affect nursing staff performance. Recommendations: Management should provide and maintain at the workplace, adequate plant and system of work that are safe and without risk to health.